2003
DOI: 10.1016/s1521-690x(02)00103-3
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-oestrogens

Abstract: Phyto-oestrogens are oestrogenic compounds found in plants and consist of isoflavones, lignans and coumestans. Epidemiological studies provide evidence for a protective role of isoflavones, and to a lesser extent lignans, against the development of numerous chronic diseases, including several cancers, cardiovascular disease and osteoporosis. The structural similarity of phyto-oestrogens to endogenous oestrogens has prompted the hypothesis that phyto-oestrogens exert hormonal or anti-hormonal effects relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 127 publications
1
91
0
9
Order By: Relevance
“…The interest in these compounds started in the 80 th of the last century, when epidemiological studies comparing Western and Asian diets indicated that a phytoestrogenrich diet may prevent diseases such as breast and prostate cancer, cardiovascular diseases, osteoporosis, menopausal symptoms, etc. (Duncan et al 2003;Cornwell et al 2004). The putative beneficial health effects of isoflavones are based on their structural similarity to the mammalian estrogen 17β-estradiol.…”
mentioning
confidence: 99%
“…The interest in these compounds started in the 80 th of the last century, when epidemiological studies comparing Western and Asian diets indicated that a phytoestrogenrich diet may prevent diseases such as breast and prostate cancer, cardiovascular diseases, osteoporosis, menopausal symptoms, etc. (Duncan et al 2003;Cornwell et al 2004). The putative beneficial health effects of isoflavones are based on their structural similarity to the mammalian estrogen 17β-estradiol.…”
mentioning
confidence: 99%
“…또한, genistein은 estrogen과 유사한 구조를 가짐으로써 estrogen receptor-β에 높 은 친화도를 가지고 있으며, 여성호르몬 유사 작용이 있어 식 물성 에스트로겐(phytoestrogen) 이라고도 불린다 [3]. 또한, genistein은 마우스3T3-L1 전지방 세포에서 지방세포의 증식 과 지질축적을 억제하며 지방세포의 지방분해를 증가시킨다 는 연구결과들이 보고된 바 있다 [5][6][7].…”
Section: 서 론unclassified
“…They also occur naturally in soy as their glycosides, named daidzin, genistin and glycitin, respectively. 3 When orally administered, isoflavones glycosides undergo enzymatic hydrolysis in the small intestine, releasing the aglycones, the moieties which are absorbed and present biologic effects. 4 In vitro studies for these aglycones have demonstrated that genistein exhibits the highest affinity for estrogenic receptors, 5 being approximately ten times more active in vivo than daidzein.…”
Section: Introductionmentioning
confidence: 99%